2018
DOI: 10.1158/1538-7445.am2018-3770
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3770: Characterization of novel dual A2A/A2B adenosine receptor antagonists for cancer immunotherapy

Abstract: Adenosine is the key immunometabolite responsible for immune tolerance in tumors. It is present in normal tissue in low concentrations, having various physiological functions. In the tumor, its concentration increases rapidly, as a result of overexpression of enzymes producing adenosine, additionally enhanced by hypoxia and inflammation. Adenosine inhibits the biological functions of T lymphocytes infiltrating the cancer tissue by binding to the A2A receptor. The affinity to A2B receptor is believed to attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…One example of a factor with broad immunosuppressive effects is the adenosine signaling axis (11), which has been shown to suppress natural killer (NK) and CD8 þ T-cell cytolytic activity while enhancing suppressive macrophage and dendritic cell polarization as well as Treg and myeloid-derived suppressor cell (MDSC) proliferation (12). Beginning with landmark research by Ohta and colleagues (13), a series of preclinical studies (14)(15)(16)(17)(18) have been reported and clinical trials (19)(20)(21) initiated targeting adenosine signaling. In addition, preclinical evidence supports a role for adenosine axis antagonists in chimeric antigen receptor T-cell therapy (22), adoptive cell therapy (13), and cancer vaccines (23).…”
Section: Introductionmentioning
confidence: 99%
“…One example of a factor with broad immunosuppressive effects is the adenosine signaling axis (11), which has been shown to suppress natural killer (NK) and CD8 þ T-cell cytolytic activity while enhancing suppressive macrophage and dendritic cell polarization as well as Treg and myeloid-derived suppressor cell (MDSC) proliferation (12). Beginning with landmark research by Ohta and colleagues (13), a series of preclinical studies (14)(15)(16)(17)(18) have been reported and clinical trials (19)(20)(21) initiated targeting adenosine signaling. In addition, preclinical evidence supports a role for adenosine axis antagonists in chimeric antigen receptor T-cell therapy (22), adoptive cell therapy (13), and cancer vaccines (23).…”
Section: Introductionmentioning
confidence: 99%
“…The failure of preladenant in a phase 1 trial, however, suggested that A 2A R antagonists originally developed for neurological conditions may not be sufficiently efficacious for cancer treatment . Studies from iTeos and Selvita research groups have revealed that some of the A 2A R antagonists designed for Parkinson’s disease dramatically lost potency in a high adenosine environment. , Generally, much higher extracellular adenosine levels are present in the TME than in the conditions of Parkinson’s disease. A reasonable speculation is that more or stronger A 2A R antagonists are needed to overcome the elevated adenosine levels.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, CPI-444 and AZD4635 (a clinical compound to be discussed later) almost completely lost their activities in high adenosine environment, with EC 50 > 10 000 nM. 137 Notably, both compounds 43 and 44 exclusively restored the function of monocyte-derived dendritic cells (moDC cells, driven by A 2B R) compared to A 2A R antagonists such as CPI-444. Further results from in vivo testing were disclosed for compound 44.…”
Section: Oncoimmunological Effects and Binding Modes Of Previouslymentioning
confidence: 99%
See 2 more Smart Citations